The Use Of Health Behavior Apd Officer To Prevent Infection HIV AIDS - Sumarni Sumarni; Hartati Hartati; Zaenal Amirudin (Poltekkes Kemenkes Semarang, 2014)
HIV is transmitted to health-care workers in providing care to patients, especially when the rules of universal precautions and Occupational Health and Safety (K3) is not implemented. To protect ourself from health problems caused by the HIV is by using PPE (Personal Protection Equipment). Data HIV / AIDS patients in hospitals in 2011 there were 35 patients Rod, in 2012 there were 33, in 2013 there were 17 (until April) . This is a quantitative study with a cross-sectional design using interviews and questionnaires. The purpose of this study is to analyze factors that influence the behavior of health workers in the use of personal protective equipment (PPE) to prevent HIV infection. The sample of this research was 200 health workers in the Batang Public Hospital, whereas the saturated sampling technique was used in this research. Results shows that 104 (52.0%) of respondents were well behaved on the use of PPE. The related factors are knowledge, attitudes and support of influential friend. Friends-factor had OR = 13.6. Suggestions are made for health care workers in order to provide mutual support to others in the use of PPE.